2021
DOI: 10.1097/qad.0000000000002985
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α inhibition in the setting of undiagnosed HIV infection: a call for enhanced screening guidelines

Abstract: Background: Despite the risks of immunosuppression, recommendations regarding screening for HIV infection prior to initiation of biologic therapies targeting common rheumatologic disorders, including inflammatory bowel disease (IBD) and inflammatory arthritides, are limited. Few cases of patients started on biologics while living with undiagnosed HIV infection have been reported. Methods:We report three cases of patients initiated on biologics in the absence of recent or concurrent HIV screening who developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…[ 52 , 54 ]. Therefore, close collaboration between oncological, dermatological, and infectious disease specialists is sometimes mandatory for a correct management of HS [ 29 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 52 , 54 ]. Therefore, close collaboration between oncological, dermatological, and infectious disease specialists is sometimes mandatory for a correct management of HS [ 29 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the clinical and therapeutic management of HS is burdened by a high rate of clinical failures and recurrences; more so in people living with HIV [ 24 , 26 ]. Depending on the severity of the disease, its extension and patients’ comorbidities, HS treatment includes topical or systemic antibiotics (such as doxycycline, clindamycin, or erythromycin), corticosteroids, isotretinoin, antiandrogens and immunosuppressors [ 6 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 55 , 56 , 57 ]. Severe cases of HS may also require surgical removal of the lesions, thus causing difficult to accept cosmetic alterations [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents can place patients at increased risk of opportunistic infection and malignancy. 2,3 HIV directly or indirectly affects nearly all of the organ systems of the body, leading to a wide range of pathology, including HIV-associated renal diseases, enteropathies, and cancers, such as non-Hodgkin lymphoma (NHL). 4 Given this wide range of pathology and clinical manifestations, a missing HIV diagnosis may adversely affect disease management and prognosis when individuals with these conditions present for care.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…One recent case series identified undiagnosed HIV + patients receiving biologic immunosuppression and developing unexpected opportunistic infections with worsened clinical presentation. 2 For some conditions, such as secondary glomerulonephritis, immunosuppression often is unnecessary, and treatment of the underlying disorder (eg, HIV) is the first-line therapy. Despite these risks, HIV testing before immunosuppression is not universal practice: Li et al found that among cancer survivors ages 65 years and younger in the United States, only 41% had ever received HIV testing.…”
Section: Background and Objectivesmentioning
confidence: 99%